Multi-Center in-Depth Screening of Neonatal Deafness Genes: Zhejiang, China - Luhang Cai; Ya Liu; Yaping Xu; Hang Yang; Lihui Lv; Yang Li; Qiongqiong Chen; Xiaojiang Lin; Yihui Yang; Guangwei Hu; Guofeng Zheng; Jing Zhou; et al. (Frontiers in Genetics, 2021)
PurposeThe conventional genetic screening for deafness involves 9–20 variants from four genes. This study expands screening to analyze the mutation types and frequency of hereditary deafness genes in Zhejiang, China, and explore the significance of in-depth deafness genetic screening in newborns.MethodsThis was a multi-centre study conducted in 5,120 newborns from 12 major hospitals in the East-West (including mountains and islands) of Zhejiang Province. Concurrent hearing and genetic screening was performed. For genetic testing, 159 variants of 22 genes were screened, including CDH23, COL11A1, DFNA5, DFNB59, DSPP, GJB2, GJB3, KCNJ10, MT-RNR1, MT-TL1, MT-TS1, MYO15A, MYO7A, OTOF, PCDH15, SLC26A4, SOX10, TCOF1, TMC1, USH1G, WFS1, and WHRN using next-generation sequencing. Newborns who failed to have genetic mutations or hearing screening were diagnosed audiologically at the age of 6 months.ResultsA total of 4,893 newborns (95.57%) have passed the initial hearing screening, and 7 (0.14%) have failed in repeated screening. Of these, 446 (8.71%) newborns carried at least one genetic deafness-associated variant. High-risk pathogenic variants were found in 11 newborns (0.21%) (nine homozygotes and two compound heterozygotes), and eight of these infants have passed the hearing screening. The frequency of mutations in GJB2, GJB3, SLC26A4, 12SrRNA, and TMC1 was 5.43%, 0.59%, 1.91%, 0.98%, and 0.02%, respectively. The positive rate of in-depth screening was significantly increased when compared with 20 variants in four genes of traditional testing, wherein GJB2 was increased by 97.2%, SLC26A4 by 21% and MT-RNR1 by 150%. The most common mutation variants were GJB2c.235delC and SLC26A4c.919-2A > G, followed by GJB2c.299_300delAT. Homoplasmic mutation in MT-RNR1 was the most common, including m.1555A > G, m.961T > C, m.1095T > C. All these infants have passed routine hearing screening. The positive rate of MT-RNR1 mutation was significantly higher in newborns with high-risk factors of maternal pregnancy.ConclusionThe positive rate of deafness gene mutations in the Zhejiang region is higher than that of the database, mainly in GJB2c.235delC, SLC26A4 c.919-2A > G, and m.1555A > G variants. The expanded genetic screening in the detection rate of diseasecausing variants was significantly improved. It is helpful in identifying high-risk children for follow-up intervention.